Peran Ekstrakurikuler Dalam Meningkatkan Karakter Santri Pondok Pesantren - Nur Hidayat (Universitas Alma Ata, 2014)
The results showed: (1) existing extracurricular at Islamic boarding school daughter Nurul Ummah (PPNU-Pi) is the Rural Development Team (TBD) engaged in propaganda, hadroh (Azkiya'), calligraphy, and extracurricular writing (recitation). The implementation of all extracurricular have been running well, because it was done as the existing plan. (2)The Fourth extracurricular instrumental in increasing the value of the character-Pi PPNU students namely: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, reward achievement, communicative, love peace, likes to read, care about the environment, social care, and responsibility. (3)Factors supporting the implementation of extracurricular is motivation, a sense of sincerity, cohesiveness owned extracurricular students who follow and support provided by outside parties both administrators, caregivers and alumni, as well as the available infrastructure. While obstacle factors are insufficient infrastructure, the quality of human resources (HR) and declining vigor in performing activities less stable. Keywords: character, extracurricular